2020
DOI: 10.1111/vsu.13404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the medium‐ to long‐term radiographically confirmed outcome for juvenile dogs with hip dysplasia treated with double pelvic osteotomy

Abstract: Objective: To assess the medium-to long-term radiographically confirmed outcomes in juvenile dogs with hip dysplasia (HD) that did and did not undergo double pelvic osteotomy (DPO). Study design: Retrospective case-controlled.Animals: Twenty-six dogs with HD that were candidates for DPO; 22 dogs underwent DPO (16 bilateral, six unilateral); four dogs did not.Methods: Initial and follow-up radiographs of DPO candidates (2011-2017) that did and did not undergo surgery were reviewed, and the British Veterinary As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Pelvic osteotomies aim to increase femoral head‐dorsal acetabular coverage to improve joint congruency in dogs affected by hip dysplasia 3–6 . The acetabular rotation is fixed using a preangled plate 1,3–7 . The double pelvic osteotomy (DPO) may be considered an evolution of the triple pelvic osteotomy (TPO) in which a pubic ostectomy and an ilial osteotomy are performed, leaving the ischium intact 4–7 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pelvic osteotomies aim to increase femoral head‐dorsal acetabular coverage to improve joint congruency in dogs affected by hip dysplasia 3–6 . The acetabular rotation is fixed using a preangled plate 1,3–7 . The double pelvic osteotomy (DPO) may be considered an evolution of the triple pelvic osteotomy (TPO) in which a pubic ostectomy and an ilial osteotomy are performed, leaving the ischium intact 4–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Double pelvic osteotomy had therefore been exclusively performed in young dogs ranging from 4.5 to 9 months of age 4 . Age is generally used as a selection criterion for pelvic osteotomies for assessing whether the dog already has secondary osteoarthritis 5 . However, we contend that osteoarthritic changes should be assessed regardless of the dog's age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It showed that DPO significantly reduced the progression of radiographically confirmed coxofemoral osteoarthritis; however, the radiographic changes were not correlated with the clinical outcome. 31 Plates designed specifically for DPO have been commercially available since 2008 and were developed to reduce the incidence of complications seen when triple pelvic osteotomy plates were used for DPO. The main difference between triple pelvic osteotomy and DPO plates is the pattern of fixation of the cranial and caudal parts of the plate or the number of screws in the caudal part (4 instead of 3).…”
Section: Introductionmentioning
confidence: 99%